Neuromuscular, hormonal, and metabolic responses to different plyometric training volumes in rugby players - Cadore, E. L.; Pinheiro, E.; Izquierdo, M.; Correa, C. S.; Radaelli, R.; Martins, J. B.; Lhullier, F. L. R.; Laitano, O.; Cardoso, M.; Pinto, R. S. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to investigate the effect of different volumes of plyometric exercise (i.e., 100, 200, or 300 hurdle jumps) on acute strength and jump performance and on the acute hormonal and lactate responses in rugby players. Eleven young male elite rugby players (age, 23.5 ± 0.9 years; height, 173 ± 4.8 cm) volunteered for the study. Maximal isometric peak torque (PT), maximal rate of force development (RFD), squat jump (SJ), and drop jump (DJ) performance were assessed before and 5 minutes, 8 hours, and 24 hours after 100, 200, or 300 jumps. In addition, total testosterone (TT), cortisol (COR), and lactate were measured before and after the 3 different plyometric exercise volumes. There were significant decreases in the PT (p < 0.02) and maximal RFD (p < 0.001) 5 minutes, 8 hours, and 24 hours after 100, 200, and 300 jumps, with no differences between the exercise volumes. Additionally, there were significant decreases in the SJ (p < 0.001) and DJ (p < 0.01) performances 24 hours after 100, 200, and 300 jumps, with no differences between the exercise volumes. However, there were significant increases in the TT (p < 0.001), COR (p < 0.05), and lactate (p < 0.001) after 100, 200, and 300 jumps, with no differences between the exercise volumes. All plyometric exercise volumes (100, 200, and 300 jumps) resulted in similar neuromuscular, metabolic, and hormonal responses.